Assessment of Glenohumeral Subluxation in Poststroke Hemiplegia: Comparison Between Ultrasound and Fingerbreadth Palpation Methods. Issue 11 (1st November 2014) - Kumar, Praveen; Mardon, Marianne; Bradley, Michael; Gray, Selena; Swinkels, Annette
Abstract : Background: Glenohumeral subluxation (GHS) is a common poststroke complication. Treatment of GHS is hampered by the lack of objective, real-time clinical measurements. Objective: The aims of this study were: (1) to compare an ultrasound method of GHS measurement with the fingerbreadth palpation method using a receiver operating characteristic curve (ROC) and (2) to report the sensitivity and specificity of this method. Design: A prospective study was conducted. Setting: The study was conducted in local hospitals and day centers in the southwest of England. Patients: One hundred five patients who had one-sided weakness following a first-time stroke (51 men, 54 women; mean age=71 years, SD=11) and who gave informed consent were enrolled in the study. Measurements: Ultrasound measurements of acromion–greater tuberosity (AGT) distance were used for the assessment of GHS. Measurements were undertaken on both shoulders by a research physical therapist trained in shoulder ultrasound with the patient seated in a standardized position. Fingerbreadth palpation assessment of GHS was undertaken by a clinical physical therapist based at the hospital, who also visited the day centers. Results: The area under the ROC curve was 0.73 (95% confidence interval [95% CI]=0.63, 0.83), suggesting that the ultrasound method has good agreement compared with the fingerbreadth palpation method. A cutoff point of ≥0.2 cm AGT measurement difference between affected and unaffected shoulders generated a sensitivity of 68% (95% CI=51%, 75%), a specificity of 62% (95% CI=47%, 80%), a positive likelihood ratio of 1.79 (95% CI=1.1, 2.9), and a negative likelihood ratio of 0.55 (95% CI=0.4, 0.8). Limitations: Clinical therapists involved in the routine care of patients conducted the fingerbreadth palpation method. It is likely that they were aware of the patients' subluxation status. Conclusion: The ultrasound method can detect minor asymmetry (≤0.5 cm) and has the potential advantage over the fingerbreadth palpation method of identifying patients with minor subluxation.